Abortions induced by inserting wooden stick - Pant, PR; Sharma, J; Mananandher, BL; Sharma, NR; Shrestha, R (Journal of Institute of Medicine Nepal, 2007)
Background: Nepal suffers from one of the highest maternal mortality rate in the world, and the practice of unsafe abortion is responsible for more than 50% of these maternal deaths. Before legalization of abortion in2002 though it was criminal act under any circumstances thousands of abortions were done illegally in the country by expert doctors to peon by different methods. Complications of abortions depend upon gestational age, service provider, method, place of abortion. According to a nationwide survey done by CREHPA in 1997 revealed that 20% of the women prisoners against 0.3 men prisoners were there for charge of abortion or infanticide. According to Measham maternal mortality is highest in cases when the abortion is done by foreign objects in to the uterine cavity. Key words: Induced abortion; complications; unsafe abortion. The full text of this paper is available at Journal of Institute of Medicine website